2011
DOI: 10.1007/s00464-011-1858-z
|View full text |Cite
|
Sign up to set email alerts
|

Partially covered self-expanding metal stent for unresectable malignant extrahepatic biliary obstruction: results of a large prospective series

Abstract: The partially covered SEMS was easily inserted, had a high clinical success rate, and prevented tumor ingrowth. The incidence of possible complications related to stent coverage, namely, migration, pancreatitis, and cholecystitis, was lower than in previously published series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Median stent patency for partially covered self-expanding metal stents in another study of patients with unresectable malignant extrahepatic biliary obstruction was reported at 138.9 days (18); an additional study evaluated stent patency with covered (mean patency, 225 days) and uncovered (mean patency, 193 days) stents (19). It should be noted, however, that the mean survival for these studies was higher compared to our study, at 141.7 days and 255/237 (covered/uncovered) days, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Median stent patency for partially covered self-expanding metal stents in another study of patients with unresectable malignant extrahepatic biliary obstruction was reported at 138.9 days (18); an additional study evaluated stent patency with covered (mean patency, 225 days) and uncovered (mean patency, 193 days) stents (19). It should be noted, however, that the mean survival for these studies was higher compared to our study, at 141.7 days and 255/237 (covered/uncovered) days, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality was 2%, similar to other studies. This paper demystifies some complications that may raise doubts on the usefulness of metallic coated stents in clinical practice, and demonstrates their high effectiveness and safety (24).…”
Section: Coated Metallic Versus Uncoated Metallic Stentsmentioning
confidence: 88%
“…There are three important limitations to this study. Partially covered stents that do not cause obstruction of the pancreatic duct opening have also recently been used (Gómez-Oliva et al 2012). Use of these stents may achieve long-term patency with fewer complications.…”
Section: Discussionmentioning
confidence: 99%